Evaluasi Pelatihan Vokasional Agribisnis dalam Meningkatkan Akses Pasar Produk Pertanian - Astri Shabrina; Citra Rianzani; Tika Dewi; Bambang Irawan; Ade Rahmad Kurniawan (Bulletin of Community Engagement, 2021)
This study aims to evaluate the effectiveness of agribusiness vocational training in improving market access for farmers, particularly in the Lampung region, in 2021. A descriptive qualitative approach was used, with data collection techniques including in-depth interviews, field observations, and documentation. The results indicate that this training had a positive impact on changing farmers' behavior in marketing agricultural products, particularly through improved packaging skills, digital promotion, and the use of online platforms such as social media and e-commerce. Farmers who participated in the training were able to expand their marketing networks, improve product competitiveness, and increase income. However, the success of the training is highly dependent on local institutional support, digital literacy, and the availability of technological infrastructure. This study concludes that agribusiness vocational training is an effective empowerment strategy for promoting farmer economic independence, but it needs to be complemented by ongoing mentoring and policy integration at the local level.